Use of Geographic Information System Mapping in the Examination of Specialized Low Vision Resources and Areas of Need in Michigan. (January 2021) - Connors, Elyse; Willard, Amber E.; Baker, Kathleen M.; Debiak, Katie; Beranek, Renee; Roodbar, Sam
Introduction: The number of adults with visual impairments (i.e., blindness or low vision) is increasing, especially with the aging of the population. Although awareness of vision loss as a public health problem is growing, public health budgets are decreasing. This study exemplifies the use of publicly available secondary data and geographic information system (GIS) mapping to spatially map areas of potential higher risk for vision loss and identify where specialized, low vision resources are located, by county, in Michigan. Methods: County-level, publicly available data on risk factors for low vision (health and demographic) and specialized low vision resources (medical, rehabilitation, and community) are extracted from existing public health data sets and information published on the Internet. GIS mapping is applied to visually examine potential areas of disparity between need and resources. Results: Broadly speaking, counties in Michigan with the highest number of risk factors for low vision are clustered in the center of the Lower Peninsula and on the eastern and western ends of the Upper Peninsula. Areas that have fewer resources for low vision are clustered in the thumb area and the middle to upper part of the Lower Peninsula. Resources are concentrated near the state's metropolitan areas (i.e., Detroit and suburbs, Kalamazoo, and Grand Rapids). Discussion: Maps can be helpful in locating areas of health disparities, but they need to be interpreted carefully such as by considering the county's population size. Understanding the eligibility criteria of available services can help to uncover groups of persons not being served. Implications for practitioners: With increasing need for services and shrinking budgets, strategic planning may help alleviate anticipated shortfalls in available services. Use of publicly available data and GIS mapping may be an affordable and efficient method to identify areas of need and resources, for targeted public health efforts in vision.